ICOSLG-associated immunological landscape and diagnostic value in oral squamous cell carcinoma: a prospective cohort study - Dong, Yuexin; Hu, Xinyang; Xie, Shixin; Song, Yuxian; He, Yijia; Jin, Wanyong; Ni, Yanhong; Wang, Zhiyong; Ding, Liang (Frontiers in Cell and Developmental Biology, 2023)
We previously reported that stroma cells regulate constitutive and inductive PD-L1 (B7-H1) expression and immune escape of oral squamous cell carcinoma. ICOSLG (B7-H2), belongs to the B7 protein family, also participates in regulating T cells activation for tissue homeostasis via binding to ICOS and inducing ICOS+ T cell differentiation as well as stimulate B-cell activation, while it appears to be abnormally expressed during carcinogenesis. Clarifying its heterogeneous clinical expression pattern and its immune landscape is a prerequisite for the maximum response rate of ICOSLG-based immunotherapy in a specific population.This retrospective study included OSCC tissue samples (n=105) to analyze the spatial distribution of ICOSLG. Preoperative peripheral blood samples (n=104) and independent tissue samples (n=10) of OSCC were collected to analyze the changes of immunocytes (T cells, B cells, NK cells and macrophages) according to ICOSLG level in different cellular contents.ICOSLG is ubiquitous in tumor cells (TCs), cancer-associated fibroblasts (CAFs) and tumor infiltrating lymphocytes (TILs). Patients with high ICOSLGTCs or TILs showed high TNM stage and lymph node metastasis, which predicted a decreased overall or metastasis-free survival. This subcohort was featured with diminished CD4+ T cells and increased Foxp3+ cells in invasive frontier in situ, and increased absolute numbers of CD3+CD4+ and CD8+ T cells in peripheral blood. ICOSLG also positively correlated with other immune checkpoint molecules (PD-L1, CSF1R, CTLA4, IDO1, IL10, PD1).Tumor cell-derived ICOSLG could be an efficient marker of OSCC patient stratification for precision immunotherapy.